A population based study on health conditions associated with the use of benzodiazepines among older adults (The Bambuí Health and Aging Study) Estudo de base populacional sobre condições de saúde associadas ao uso de benzodiazepínicos em idosos (Projeto Bambuí) - Jussara Mendonça Alvarenga; Antônio Ignácio de Loyola Filho; Josélia Oliveira Araújo Firmo; Maria Fernanda Lima-Costa; Elizabeth Uchoa (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2009)
The aim of this study was to assess the health conditions and use of health services among elderly users of benzodiazepines. The study was carried out in the city of Bambuí in Minas Gerais State, Brazil. Of 1,742 inhabitants aged over 60, 1,419 participated in the study. Information about benzodiazepine and the use of other medications was obtained by means of interviews and checking medication packaging. After adjustments for confounding variables, benzodiazepine remained significantly associated with poorer self reported health (prevalence ratio = 1.94 and 2.04 for reasonable and bad/very bad health, respectively), common mental disorders (1.33), myocardial infarction (1.42), number of doctor visits in the previous 12 months (1.90 and 2.24 for 2-3 and 4+ visits, respectively) and concomitant use of other medications (1.84 and 1.83 for 2-4 and 5+ medications). The results showed that the factors associated with the use of benzodiazepine were similar to those observed in the elderly in higher income countries. The concomitant use of benzodiazepines and two or more medications was highly prevalent (59.5%), characterizing a situation of risk, which deserves attention as a public health problem. O objetivo deste estudo foi determinar condições de saúde e usos de serviços de saúde associados ao uso de benzodiazepínicos entre idosos. O estudo foi conduzido na cidade de Bambuí, Minas Gerais, Brasil. Entre os 1.742 residentes com idade > 60 anos, 1.419 participaram do estudo. Informações sobre o uso de benzodiazepínicos e de outros medicamentos foram obtidas por meio de entrevista e verificação da embalagem. Após ajustamentos por variáveis de confusão, o uso de benzodiazepínicos permaneceu significativamente associado com pior auto-avaliação da saúde (razões de prevalência = 1,94 e 2,04 para razoável e ruim/muito ruim, respectivamente), transtornos mentais comuns (1,33), infarto do miocárdio (1,42), número de visitas médicas nos últimos 12 meses (1,90 e 2,24 para 2-3 e 4+ visitas, respectivamente) e uso concomitante de outros medicamentos (1,84 e 1,83 para 2-4 e 5+ medicamentos). Os resultados mostraram que os fatores associados ao uso de benzodiazepínicos foram semelhantes aos observados em idosos de países com renda mais alta. O uso concomitante de benzodiazepínicos e de outros dois ou mais medicamentos foi freqüente (59,5%), caracterizando uma situação de risco que merece atenção como problema de saúde pública.